Wild tracks! : a guide to nature's footprints - Arnosky, Jim. (New York : Sterling, 2008)
Presents detailed illustrations of life-size paw, claw, and hoof prints; and explains how to identify tracks and how fast the animal might be traveling.
Includes four large gatefolds.
Kirkus Starred.
5.9
3-6
Keywords: Animal tracks -- Juvenile literature; Toy and movable books -- Specimens; Animal tracks; Toy and movable books; Animal tracks; Toy and movable books